Status and New Data of the Geochemical Determination of the pp-Neutrino Flux by LOREX. (27th December 2012) - Pavićević, M. K.; Bosch, F.; Amthauer, G.; Aničin, I.; Boev, B.; Brüchle, W.; Cvetković, V.; Djurčić, Z.; Henning, W. F.; Jelenković, R.; Pejović, V.; Weiss, A.
Abstract : LOREX (LORandite EXperiment) addresses the determination of the solar (pp) neutrino flux during the last four million years by exploiting the reaction 205 Tl + ν e → 205 Pb + e - with an incomparably low-energy threshold of 50 keV for the capture of solar neutrinos. The ratio of 205 Pb/ 205 Tl atoms in the Tl-bearing mineral lorandite provides, if corrected for the cosmic-ray induced background, the product of the flux of solar neutrinos and their capture probability by 205 Tl, averaged over the age of lorandite. To get the mean solar neutrino flux itself, four problems have to be addressed: (1) the geological age of lorandite, (2) the amount of background cosmic-ray-induced 205 Pb atoms which strongly depends on the erosion rate of the lorandite-bearing rocks, (3) the capture probability of solar neutrinos by 205 Tl and (4) the extraction of lorandite and the appropriate technique to "count" the small number of 205 Pb atoms in relation to the number of 205 Tl atoms. This paper summarizes the status of items 1 (age) and 3 (neutrino capture probability) and presents in detail the progress achieved most recently concerning the items 2 (background/erosion) and 4 ("counting" of 205 Pb atoms in lorandite).